![image](https://tex.z-dn.net/?f=lgsin2x%3Dlgcosx%5C%5C+%5Cleft+%5C%7B+%7B%7Bsin2x%3E0%7D+%5Catop+%7Bcosx%3E0%7D%7D+%5Cright.+%5C%5C+sin2x%3Dcosx%5C%5C+2sinx%2Acosx%3Dcosx%5C%5C+cosx%282sinx-1%29%3D0%5C%5C+cosx%3D0%5C%5C+sinx%3D%5Cfrac%7B1%7D%7B2%7D%5C%5C+)
0} \atop {cosx>0}} \right. \\ sin2x=cosx\\ 2sinx*cosx=cosx\\ cosx(2sinx-1)=0\\ cosx=0\\ sinx=\frac{1}{2}\\ " alt="lgsin2x=lgcosx\\ \left \{ {{sin2x>0} \atop {cosx>0}} \right. \\ sin2x=cosx\\ 2sinx*cosx=cosx\\ cosx(2sinx-1)=0\\ cosx=0\\ sinx=\frac{1}{2}\\ " align="absmiddle" class="latex-formula">
Откуда с учетом выше стоящего неравенства получаем